Spatially Integrated Social Research and Official Statistics: Methodological Remarks and Empirical Results on Local Development - Okrasa, Włodzimierz (Comparative Economic Research. Central and Eastern Europe, 2013)
This paper aims to elucidate some aspects of confluence of the developments in modern methods of spatial analysis and in the public statistics’ data generating processes, along with empirical illustration of these interconnections from the development policy evaluation standpoint. Especially, how the growing availability of data at the finest level of territorial division (such as commune/gmina-level data within the Local Data Bank system) may improve decisional processes at the regional and local level, while paying special attention to allocation of resources assuming geographic system of targeting public support or intervention. Three interrelated questions that are empirically treated in the context of both β-convergence and σ-convergence issues at the local level involve (i) measurement of the level of local (under)development /local deprivation; (ii) assessment of how responsive and equitable are distributive policies in the domain of area-addressed public resources; and (iii) evaluation of their impacts in terms of convergence and social cohesion, which are among chief objectives of development policy (especially in the ‘new’ EU member states).